2003
DOI: 10.1029/2002jc001377
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coastal effects, bottom topography, stratification, wind period, and mixing upon the propagation of internal waves and the profile of wind‐induced currents

Abstract: [1] A three-dimensional model in cross-sectional form is used to examine the influence of wind period, stratification and bottom topography upon internal wave generation and wind-induced current profiles in the coastal ocean. Calculations with fixed vertical diffusion coefficients and with a turbulence energy model are performed. These show that besides the wind period influencing the depth of penetration of the wind's momentum, as in a point model, it determines the offshore extent of internal waves generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Similarly, displacements of the density surfaces gives propagating near-inertial internal waves with a speed of order (g¢h) 1/2 with g¢ the reduced gravity (Millot and Crepon 1981). As shown by and Xing and Davies (2003), the combination of the inertial oscillations in the surface well-mixed layer, and the free surface pressure gradient associated with the surface gravity wave is responsible for producing the observed 180°phase shift in inertial oscillations across the thermocline. In addition to these inertial oscillations, nearinertial internal waves at a frequency of order 1.05f (where f is the inertial frequency) propagate away from the coastal generation region.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Similarly, displacements of the density surfaces gives propagating near-inertial internal waves with a speed of order (g¢h) 1/2 with g¢ the reduced gravity (Millot and Crepon 1981). As shown by and Xing and Davies (2003), the combination of the inertial oscillations in the surface well-mixed layer, and the free surface pressure gradient associated with the surface gravity wave is responsible for producing the observed 180°phase shift in inertial oscillations across the thermocline. In addition to these inertial oscillations, nearinertial internal waves at a frequency of order 1.05f (where f is the inertial frequency) propagate away from the coastal generation region.…”
Section: Introductionmentioning
confidence: 86%
“…On the shelf the elevation pressure gradient associated with the surface gravity wave that propagates from the coast drives a significant current, giving rise to inertial oscillations at depth which are phase-lagged by 180°from the surface. For a given sea-surface elevation gradient, in the absence of friction Xing and Davies 2003), showed that the magnitude of these oscillations below the thermocline was reduced as water depth increased, due to the fact that the elevation pressure gradient acted over the whole water column. In shallow-water and nearcoastal regions, both frictional effects and coastal inhibition reduce the magnitude of the oscillations below the thermocline, giving rise to the near-bed maxima in hðu À huiÞ 2 i, shown in Fig.…”
Section: Spatial Distribution Of Wind-forced Flow (Diagnostic Model)mentioning
confidence: 96%
See 3 more Smart Citations